Generic Pest Risk Analysis for Potato in Nepal - Mahto, Baidya Nath (Journal of Nepal Agricultural Research Council, 2017)
Pest Risk Analysis (PRA) is the process of evaluation for biological and economic evidences in order to determine whether a pest should be regulated under phyto-sanitary measures. The present mini review highlights the potential potato pathogen list recorded in Nepal harmful for potato production and productivity. At global scale altogether 135 potential quarantine pests (PQP) for potato has been recorded, while in Nepal only 92 PQP were recorded. Out of those 52, 13 and 27 were fungi, bacteria and viruses respectively. Among the 92 PQP, 34, 30 and 13 were considered at high, medium and lower risk type pathogens for potato. There was no information available on other 15 PQP. Journal of Nepal Agricultural Research Council Vol.3 2017: 32-37